(untitled) (Revista Latino-Americana de Enfermagem, 2004)
This study aims to explore the experiences of children and adolescents with cancer during the intrathecal chemotherapy phase, by means of a qualitative approach. Empirical data were collected on the basis of semi-structured interviews. Study participants were eleven children/adolescents who received intrathecal chemotherapy, between 07 and 16 years old, from both genders, attended at a hospital school in the interior of São Paulo State, Brazil. Results converged towards the following issues: intrathecal routine; fear, pain and relief fantasies and strategies. This study gave access to important information with a view to caring for children/adolescents during the intrathecal chemotherapy phase, which is considered as one of the most stressing situations. With respect to nursing implications, we identified the vital nature of information for children/adolescents with cancer since this makes it possible to minimize uncertainties and negative feelings and makes them collaborate and participate in treatment.